1983
DOI: 10.1159/000123439
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Pineal Gland Modulation of the Neuroendocrine-Thyroid Axis

Abstract: Experiments with rats and hamsters have provided evidence for an inhibitory action of the pineal gland on the neuroendocrine-thyroid axis. While maintenance of these animals in short photoperiod results in reduced levels of circulating thyroxin (T4), pinealectomy restores the levels to normal. Recent studies suggest that an active pineal gland produces a substance which inhibits thyrotrophin-releasing hormone release from the hypothalamus. Several investigators have concluded that endogenous melatonin, produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(30 citation statements)
references
References 66 publications
2
28
0
Order By: Relevance
“…There are also reports supporting the view that the pineal gland, via melatonin, has a modulatory effect on both gonadal and thyroid functions. Injections of melatonin for periods of 3-10 weeks reduced plasma thyroxine and TSH concentrations in hamsters, with the effects on gonadal and thyroid function being observed simultaneously (Vriend et al, 1979(Vriend et al, , 1982Vriend, 1983). Creighton & Rudeen (1988) observed that the effects of melatonin on the pituitary-gonadal and pituitary-thyroid axes were independently mediated via the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…There are also reports supporting the view that the pineal gland, via melatonin, has a modulatory effect on both gonadal and thyroid functions. Injections of melatonin for periods of 3-10 weeks reduced plasma thyroxine and TSH concentrations in hamsters, with the effects on gonadal and thyroid function being observed simultaneously (Vriend et al, 1979(Vriend et al, , 1982Vriend, 1983). Creighton & Rudeen (1988) observed that the effects of melatonin on the pituitary-gonadal and pituitary-thyroid axes were independently mediated via the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…The secretion of these hormones is on a circadian basis; their levels vary with the time of day and LD cycle as did the effect of melatonin in vivo. Furthermore, exogenous melatonin itself might influence the synthesis or release of these hormones (24).…”
Section: Rana Temporaria (15) Rana Ridibunda (5) Andmentioning
confidence: 99%
“…Antagonism of thyroid hormone action by melatonin is suggested by the finding that T4 was more effective when given in the light (4,27) and that a 1 hr light pulse during the early dark of a 12L : 12D cycle partially counteracted the negative effect of administering T4 at that time (28). In rats, the pineal inhibited the neuroendocrine-thyroid axis (20,24). Since light stimulated thyroid gland activity in Rana catesbeiana (12), such inhibition might also exist in amphibians.…”
Section: Introductionmentioning
confidence: 99%
“…The Syrian hamster is the species most often used to demonstrate the effk -ts of the pineal gland on the reproductive system and thyroid function [Reiter, 1980: M. Vriend, 1983). Previou, pineal melatonin content profiles [Panke ct al., 1979;Tamarkin et al, 19791 and the more recently studied serum concentration profiles [Brown et al 1981;Vaughan ct al., 1985a] both are characterized by a nocturnal melatonin surge in the late part of the dark phase in this species.…”
Section: Introductionmentioning
confidence: 99%